Tutor in Common Room – pedagogue in the shadow? - Kasprzak, Michalina (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
Common Rooms as outpost of daily support are places, where are attending children and young people of all ages. They come often from disadvantaged backgrounds, difficult backgrounds as well as marginalized and excluded backgrounds. In order to conduct efficient and effective process to aid and support children and young people, classes and free time are organized by tutors in Common Rooms. However, legal regulation in Poland do not regulate all the issues associated with the practice tutor in Common Room. In this paper, I would like to present the current profile of tutor in Common Room, based on the results of own research. At the end I would like to present my proposals for methods and forms how work with children and young people, that makes that pedagogue do not remain in a shadow, but he or she could be pleased and satisfied from work with children and young people in Common Rooms.